Psychiatric Disorders New Frontiers in Affective Disorders - Schoepf, Dieter (IntechOpen, 2013)
Affective disorders are a subject of interest to clinicians for more than a century. The awareness of an urgent need for an evidence-based "personalized" approach of treatment is growing in the field of psychiatry. This book brings together leading experts to create a volume of equal interest and usefulness to students, clinicians and researchers alike, which should serve as common knowledge. Specific themes of major depression, bipolar disorder, and schizoaffective disorder are critically reviewed, addressing topics such as neurobiological mechanisms underlying the pathogenesis, treatment resistant depression, translational research and challenging stigma of serious mental illness. Particular emphasis is put on novel developments in Cognitive-Behavioral Therapy and on attention to causal mechanisms of behaviour change in the Cognitive Behavioral Analysis System of Psychotherapy.